2017
DOI: 10.1002/hep.29238
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1/HSF1/HSP pathway is essential for exenatide‐alleviated, lipid‐induced hepatic endoplasmic reticulum stress

Abstract: The SIRT1/heat shock factor 1/HSP pathway is essential for exenatide-alleviated, lipid-induced ER stress and hepatic steatosis, which provides evidence for a molecular mechanism to support exenatide and incretin mimetics as promising therapeutics for obesity-induced hepatic steatosis. (Hepatology 2017;66:809-824).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 47 publications
(115 reference statements)
1
56
1
Order By: Relevance
“…Glucagon‐like peptide‐1 receptor agonists have a beneficial effect on attenuating hepatic steatosis, but the exact mechanisms have not been clearly defined . Recent studies reported that Sirt1 could be a crucial mediator for GLP‐1Ra‐mediated NAFLD, but they did not show how GLP‐1Ras modulate Sirt1 to attenuate fatty liver . We found that liraglutide upregulated the expression of ATGL and Sirt1 to antagonize lipid accumulation in vivo and in vitro .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Glucagon‐like peptide‐1 receptor agonists have a beneficial effect on attenuating hepatic steatosis, but the exact mechanisms have not been clearly defined . Recent studies reported that Sirt1 could be a crucial mediator for GLP‐1Ra‐mediated NAFLD, but they did not show how GLP‐1Ras modulate Sirt1 to attenuate fatty liver . We found that liraglutide upregulated the expression of ATGL and Sirt1 to antagonize lipid accumulation in vivo and in vitro .…”
Section: Discussioncontrasting
confidence: 57%
“…S1d–f). Depending on the regulation of ATGL, Sirt1 mediates the role of GLP‐1Ra in hepatic steatosis in HFD‐induced WT mice . Therefore, liraglutide could mitigate intracellular lipids by regulating the ATGL/Sirt1 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic messenger RNA (mRNA) expression of several ER stress markers were analyzed for the HFD and HFD + VC groups. Sirtuin 1 ( Sirt1 ) has recently been shown to be a negative regulator of ER stress . Indeed, here VC significantly decreased Sirt1 expression compared to the HFD controls.…”
Section: Resultsmentioning
confidence: 71%
“…Downregulation of SIRT1 has been suggested to cause a vascular/endothelial ERS [60]. The SIRT1 pathway has also been shown to play an essential role in the exenatide-induced alleviation of the lipid-induced ERS and hepatic steatosis [61]. In addition, Kang, X. et al reported that SIRT1 inhibition mainly induced the PERK-eIF-2alpha-CHOP axis of the ERS response in the growth-plate chondrocytes, while the EX527 or SIRT1 siRNA-mediated inhibition of metatarsal growth and growth-plate chondrogenesis was partly neutralized by a chemical chaperone that attenuates the ERS [62].…”
Section: Discussionmentioning
confidence: 99%